EFFECT OF SELECTED FACTORS ON LONGEVITY IN CATTLE: A REVIEW - J. Olechnowicz; P. Kneblewski; J. M. Jaśkowski; J. Włodarek (Journal of Animal and Plant Sciences, 2016)
This review presents genetic, phenotypic, environmental and other factors influencing functional longevity in dairy cattle. High yielding cows show a lower risk of culling than low producing cows. Cows with a lower milk yield have an approximately 2.7 times greater risk of culling as compared to cows with an average milk production. Genetic estimation of the length of productive life is possible in both large and small herds. In small herds the genetic effect may be affected by residual effects. Strong relationships with functional longevity in cows have been found for the mammary gland, feet and legs. The udder depth, rear udder and rear udder attachment have the most important effects on the length of productive life. Similarly, cows with a sound conformation of rear legs, the fetlock and feet reach a longer productive life.  Age at first calving, herd size, and region of the country have a smaller effect on cow longevity; however, the recommended age of first calving is 24 months or less. The lower age at first calving is associated with lower production in the first lactation. Other traits influencing longevity of cows include calf mortality (average 8% and neonatal mortality of female calves of 3.4%), difficult calving, as well as male or twin births, high and low milk urea nitrogen concentration and lactose percentages, as well as inbreeding, which has a significant effect on reducing longevity of cows. Improved longevity can result in an increased productivity of the herd, because replacement, reproduction and veterinary costs are lowered, while mean milk production of the herd is increased.
Keywords: cows; longevity; culling; body conformation traits; economic evaluation